Level of critical thinking ability in solving numeration problems in the minimum competency assessment - Lubis, Siti Masyitoh Azzahra; Permatasari, Dian (Universitas Islam Negeri Raden Intan Lampung, 2023)
Minimum Competency Assessment (MCA) is a form of evaluation of the education system launched by the government in order to measure the achievement of students' cognitive learning outcomes in literacy and numeracy abilities. MCA numeration is related to critical thinking skills. This study aims to describe the level of students' critical thinking skills in solving the MCA numeration questions. This type of research is descriptive-qualitative research. Data collection techniques in the form of written tests and interviews with test instruments are MCA numeration questions with four questions. The data analysis technique was carried out by giving tests, then interviewing the selected subjects to find out more about critical thinking skills, and then describing the results. The results showed that the level of critical thinking ability of class VIII students in solving MCA numeration questions in the number domain met the same criteria, namely the criteria of focus, reason, and situation. Domain algebra found that students have various levels of critical thinking skills with criteria that meet the criteria of focus and reason. In the geometry domain, it was found that students had a low ability to solve geometric problems, and in the uncertainty data domain, students only reached conclusions without giving reasons.